CHOOSING OF OPERATING FREQUENCY OF EDDY CURRENT THICKNESS METER WITH SUPERIMPOSED TRANSDUCER - A. V. Chernyshev (Приборы и методы измерений)
It is shown that when using eddy current thickness meter with superimposed transducer the maximal thickness of the conductive sheets or conductive surface layers of a two-layer wares, which may be controlled with selected frequency of excitation current of the transducer, can be estimated based on the magnitude of the penetration depth of a plane electromagnetic wave in the half-space, the specific electrical conductivity and the relative magnetic permeability of which is equal to the values of these parameters in a controlled surface layer or sheet of two-layer ware.